2006
DOI: 10.3748/wjg.12.4888
|View full text |Cite
|
Sign up to set email alerts
|

Triple, standard quadruple and ampicillin-sulbactam-based quadruple therapies for H pylori eradication: A comparative three-armed randomized clinical trial

Abstract: AIM:To compare the effectiveness of triple, standard quadruple and ampicillin-sulbactam-based quadruple therapies for H pylori eradication in a comparative threearmed randomized clinical trial. METHODS:A total of 360 H pylori -positive patients suffering from dyspepsia and aging 24-79 years with a median age of 42 years were enrolled in the study and randomly allocated into the following three groups: group A (n = 120) received a standard 1-wk triple therapy ( Chi-square test with the consideration of P < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…The combination of ampicillin-sulbactum (ampicillin 225 mg and sulbactum 150 mg bid.) has equal or higher efficacy in quadruple therapy, so ampicillin-sulbactum can be considered in cases of amoxicillin resistant H. pylori strains [59].…”
Section: Standard Therapymentioning
confidence: 99%
“…The combination of ampicillin-sulbactum (ampicillin 225 mg and sulbactum 150 mg bid.) has equal or higher efficacy in quadruple therapy, so ampicillin-sulbactum can be considered in cases of amoxicillin resistant H. pylori strains [59].…”
Section: Standard Therapymentioning
confidence: 99%
“…Out of three 7-d regimens, 1 study showed acceptable eradication rates [19][20][21] . Also, out of three 10-d regimens, 2 were successful in achieving > 90% PP eradication rate [22][23][24] and out of three 14-d regimens, 1 yielded optimal results [25][26][27] .…”
Section: Standard Triple Therapymentioning
confidence: 99%
“…Out of nine 7-, 10-and 14-d Bismuth plus Metronidazole-containing quadruple regimens in Iran, none had acceptable eradication rates [20,22,26,[47][48][49][50][51][52] (Table 2). Besides, only one of the 9 studies conducted in Turkey had 90.1% PP eradication rate (Table 3) [30,[34][35][36][53][54][55][56][57] .…”
Section: Therapymentioning
confidence: 99%
“…The standard first-line therapy is a one week triple therapy amoxicillin, clarithromycin and a proton pump such as omeprazole, pantoprazole or rabeprazole, and the use of metronidazole instead of amoxycillin in those allergic to penicillin. 5,6 Resistance of H. pylori to metronidazole and macrolides has emerged worldwide and now constitutes a major problem in therapy. [7][8][9] This justifies the increasing use of culture in testing for H. pylori infection because it is the only diagnostic method that allows the susceptibility of this organism to antimicrobial agents to be assessed.…”
Section: Introductionmentioning
confidence: 99%